2007
DOI: 10.1242/jeb.008060
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of protein quality and macronutrient imbalance on nutrient balancing in an insect herbivore

Abstract: SUMMARY The present study evaluates the interactive effects of protein quality and the ratio of protein to digestible carbohydrate on herbivore performance,various aspects of nutritional homeostasis (feeding and post-ingestive regulation) and food choice. In the first experiment, final-instar caterpillars of generalist-feeding African cotton leafworm Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) were confined to one of 20 diets varying in protein:carbohydrate (P:C) ratio (35:7, 28:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 59 publications
3
42
0
6
Order By: Relevance
“…Also, on a more general note, proteincarbohydrate regulation can sometimes break down in species (Behmer, 2009). For example, Spodoptera littoralis (Boisduval, 1833) (Lepidoptera: Noctuidae) and Manduca sexta (Linnaeus, 1763) (Lepidoptera: Sphingidae) abandon protein-carbohydrate regulation in response to extreme macronutrient dilution (Lee et al, 2003;Thompson and Redak, 2005) or to changes in the protein quality of one of their available foods (Lee, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, on a more general note, proteincarbohydrate regulation can sometimes break down in species (Behmer, 2009). For example, Spodoptera littoralis (Boisduval, 1833) (Lepidoptera: Noctuidae) and Manduca sexta (Linnaeus, 1763) (Lepidoptera: Sphingidae) abandon protein-carbohydrate regulation in response to extreme macronutrient dilution (Lee et al, 2003;Thompson and Redak, 2005) or to changes in the protein quality of one of their available foods (Lee, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional value of a protein source depends on its amino acid composition. When caterpillars of Spodoptera littoralis were fed diets containing casein and zein (a poor quality plant protein), Lee (2007) found that the effect of protein quality was more strongly expressed at lower P:C ratios. The amino acid requirements of honeybees were identified by De Groot (1953), who showed that royal jelly exceeds the minimum requirements for all essential amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…caterpillar Spodoptera littoralis, which increases protein intake when dietary CA is partly replaced with zein -a protein from maize with an imbalanced amino acid composition (Lee, 2007). Compared with CA, zein also reduced HPG activation and the longevity of honeybees (Standifer et al, 1960).…”
Section: Intake Targets Of Worker Honeybees On Different Protein Sourcesmentioning
confidence: 99%